The Analysis of Software Source Code Readability: Case Study at Education of Informatics and Computer Engineering Study Program of Sebelas Maret University - Imam Setiawan; Dwi Maryono; Basori Basori (Journal of Informatics and Vocational Education, 2019)
Source code readability is a property that influences how easily a given piece of code can be read and understood. Since source code readability can affect software quality, especially maintainability, then programmers must have good sense of writing readable code. For computer science and software engineering student, they have to start learning how to write readable code in order to compete later in the industrial. Unfortunately, computer science and software engineering curriculum promotes understanding the programming paradigms of particular language, compared to write readable code. Based on its importance, we analyzed source code of software written by Education of Informatics and Computer Engineering of Sebelas Maret University students to describe its readability. We determine readability category from source code based on two programming features, variable and function writing. Each programming features involved has its own criteria so that it can be classified in the readable or less readable category. Finally, we discuss the implications of this study on learning process of Education of Informatics and Computer Engineering study program, Sebelas Maret University. For example, our data suggest to use code reviews to teach student about source code readability.